1994
DOI: 10.1902/jop.1994.65.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Attachment Loss in Community‐Dwelling Older Adults

Abstract: Since 1985, only four studies have been published that present data on attachment loss in populations. The purpose of this study was to present the incidence of attachment loss over an 18‐month period in a representative sample of community‐dwelling older adults. In addition, the utility of multivariate prediction models to distinguish between people who will and will not experience disease progression was explored. The Piedmont 65 + Dental Study of the Elderly is a longitudinal investigation of a random sub‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
135
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 10 publications
15
135
1
2
Order By: Relevance
“…This proposal has more recently been modified to emphasize the importance of synergistic interactions between potentially pathogenic bacterial species that result in the formation of a pathogenic polymicrobial plaque that is composed of one or more primary and a number of accessory bacterial pathogens expressing community virulence factors that elicit a nonresolving and tissue-destructive host response (12). We have previously demonstrated in a longitudinal human study that the imminent progression of chronic periodontitis could be predicted by increases in the relative proportions of P. gingivalis and T. denticola in subgingival plaque (14), which is consistent with other clinical studies demonstrating that the proportion of P. gingivalis in the subgingival plaque bacterial load is predictive of human disease progression (15,16). When coinoculated in small animal models of periodontitis, P. gingivalis and T. denticola exhibit a synergistic virulence (17)(18)(19).…”
supporting
confidence: 84%
“…This proposal has more recently been modified to emphasize the importance of synergistic interactions between potentially pathogenic bacterial species that result in the formation of a pathogenic polymicrobial plaque that is composed of one or more primary and a number of accessory bacterial pathogens expressing community virulence factors that elicit a nonresolving and tissue-destructive host response (12). We have previously demonstrated in a longitudinal human study that the imminent progression of chronic periodontitis could be predicted by increases in the relative proportions of P. gingivalis and T. denticola in subgingival plaque (14), which is consistent with other clinical studies demonstrating that the proportion of P. gingivalis in the subgingival plaque bacterial load is predictive of human disease progression (15,16). When coinoculated in small animal models of periodontitis, P. gingivalis and T. denticola exhibit a synergistic virulence (17)(18)(19).…”
supporting
confidence: 84%
“…Based on animal model data P. gingivalis has recently been proposed to be a "keystone pathogen" that manipulates the host response to favour the proliferation of a pathogenic polymicrobial biofilm (dysbiosis) and development of disease [19]. We have previously demonstrated in a longitudinal human study that the imminent progression of chronic periodontitis could be predicted by increases in the relative levels of P. gingivalis and/or Treponema denticola in subgingival plaque [21], which is consistent with other clinical studies demonstrating that P. gingivalis levels in subgingival plaque are predictive of human disease progression [22][23][24]. P. gingivalis is also capable of causing periodontitis in animal models of disease [25,26].…”
Section: Introductionsupporting
confidence: 84%
“…In most studies examining the relationship between gender and periodontal disease, it has been shown that the severity of periodontal disease is higher among males (18,19). Due to these results, gender differences in the prevalence and severity of periodontal disease are believed to be associated with attention and oral health care habits rather than genetic factors.…”
Section: Discussionmentioning
confidence: 99%